2013
DOI: 10.1038/bmt.2012.283
|View full text |Cite
|
Sign up to set email alerts
|

Potential adult sibling stem cell donors’ perceptions and opinions regarding an information and care model

Abstract: The first international recommendations and guidelines for the care of sibling stem cell donors were established in 2010, and have not yet been evaluated. However, a model for information and care of adult potential sibling stem cell donors (the IC model) developed and introduced at the Skåne University Hospital, Lund, Sweden, in 2005 conforms closely to them. The IC model aims to protect the privacy of potential donors, support and respect their free choice, and identify quickly those unwilling or unable to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Almost half of the donors interviewed were asked to donate by the recipient or another relative (Williams et al, ). Donors reported that the influence from relatives both facilitated and complicated their decision to undergo HLA typing (Kisch et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost half of the donors interviewed were asked to donate by the recipient or another relative (Williams et al, ). Donors reported that the influence from relatives both facilitated and complicated their decision to undergo HLA typing (Kisch et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Kisch et al () reported that information and positive care provision from Health Professionals (HP) were perceived as being important by potential donors prior to deciding whether to undergo HLA typing. The method for delivering HLA typing results varied; some donors received their typing results by regular mail; others received this information by telephone from a HP or from the recipient or another relative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations